Le WIR en Suisse : la révolte du puissant ? - Guillaume Vallet (Revue de la Régulation)
The WIR has been in existence in Switzerland as a parallel currency since 1934. It was created in the 1930’s within the context of an economic and monetary crisis. Since then, it has adapted itself to a number of economic and social changes and it continued to evolve to the point that it is now used by more than 60,000 companies in Switzerland. Such a success can be linked to a coherent economic as well as social project, which the WIR embodies. Hence this paper aims at understanding the reasons explaining its success, which strongly depends on the strength on its circulation as well as to the social values it embodies. We shed light on the fact that the WIR system is actually highly integrated to the current official Swiss monetary system. We argue that its existence and strength allow the Swiss monetary system to work efficiently: the WIR is “powerful” because it is at the core of the Swiss economic and social system, proof that monetary plurality can exist within a country’s monetary unity as well as the strength of small business companies using it, relying on the “strength of weak ties”.